1999
DOI: 10.4319/lo.1999.44.6.1540
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus availability in the Paraná floodplain lakes (Argentina): Influence of pH andphosphate buffering by fluvial sediments

Abstract: The phosphate-buffering properties and P chemistry of suspended particulate matter (SPM) collected in three geologically contrasting rivers (Bermejo, Paraguay, and Upper Paraná) are compared in order to explain the abundance of dissolved PO 4 -P in the Paraná floodplain lakes. The rivers show distinctive P-buffering capacities related to the chemical composition of their SPM. At natural pH, the linear adsorption coefficient of PO 4 -P (K d ) ranges from 0.25 liter g Ϫ1 for the Paraguay River to 1.38 liter g Ϫ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Unfortunately we have no data on nutrient concentrations in the lake water at the time of the experiments. However, it is wellknown that in the Amazon basin, floodplain lakes receive an input of inorganic nutrients from the river during the high-water period (Sioli, 1984;Junk et al, 1989;Carignan & Vaithiyanathan, 1999). The results from our experiments suggest that these annual inputs of nutrients release bacteria from nutrient limitation.…”
Section: Discussionmentioning
confidence: 52%
“…Unfortunately we have no data on nutrient concentrations in the lake water at the time of the experiments. However, it is wellknown that in the Amazon basin, floodplain lakes receive an input of inorganic nutrients from the river during the high-water period (Sioli, 1984;Junk et al, 1989;Carignan & Vaithiyanathan, 1999). The results from our experiments suggest that these annual inputs of nutrients release bacteria from nutrient limitation.…”
Section: Discussionmentioning
confidence: 52%
“…Release of P from marine sediment is prevented by adsorption of P onto Fe and precipitation with Ca forming appetite. [14][15][16] Behavior of P in soil is controlled by Al. 17) Therefore, presence and physico-chemical state of Ca, Al and Fe in the slags should complicate dissolution and adsorption of P in seawater.…”
Section: Effect Of Slags On P and Si In Seawatermentioning
confidence: 99%
“…Other studies have also observed rapid phosphate removal followed by a much slower rate of uptake which declined over time by KLL Elliott, 1999), calcite and aragonite (DeKanel and Morse, 1978); and carbonate sediments (McGlathery et al, 1994;Carignan and Vaithiyanathan, 1999;Gomez et al, 1999). Corbett et al (1999) hypothesized that adsorption/desorption reactions may explain this gradual decrease in the PO 4 removal rate.…”
Section: Discussionmentioning
confidence: 91%
“…Phosphate in such a system may be subject to adsorption, desorption, precipitation, and dissolution reactions (Froelich, 1988) and can be influenced by pH, dissolved phosphate concentrations, competing anions, and the composition of solid phase phosphate (Carignan and Vaithiyanathan, 1999). Similar buffering capacities have been documented in carbonate sediments (McGlathery et al, 1994;Carignan and Vaithiyanathan, 1999;Gomez et al, 1999).…”
Section: Discussionmentioning
confidence: 94%